Proton irradiation: a key to the challenge of N-glycosidic bond formation in a prebiotic context - Saladino, Raffaele; Bizzarri, Bruno M; Botta, Lorenzo; Šponer, Jiří; Šponer, Judit E; Georgelin, Thomas; Jaber, Maguy; Rigaud, Baptiste; Kapralov, Mikhail; Timoshenko, Gennady N; Rozanov, Alexei; Krasavin, Eugene; et al. (Scientific reports, 2017)
The formation of nucleosides in abiotic conditions is a major hurdle in origin-of-life studies. We have determined the pathway of a general reaction leading to the one-pot synthesis of ribo- and 2'-deoxy-ribonucleosides from sugars and purine nucleobases under proton irradiation in the presence of a chondrite meteorite. These conditions simulate the presumptive conditions in space or on an early Earth fluxed by slow protons from the solar wind, potentially mimicking a plausible prebiotic scenario. The reaction (i) requires neither pre-activated precursors nor intermediate purification/concentration steps, (ii) is based on a defined radical mechanism, and (iii) is characterized by stereoselectivity, regioselectivity and (poly)glycosylation. The yield is enhanced by formamide and meteorite relative to the control reaction.